A Study of Natural Metamict Yttrium Niobate as Analogue of Actinide Ceramic Waste Form. Issue 1665 (2014) - Qiuxiang, Cao; Isakov, Anton I.; Xiaodong, Liu; Krivovichev, Sergey V.; Burakov, Boris E.
ABSTRACT: Natural metamict mineral found as large (1-3 cm in size) homogeneous grains (as assumed, former single crystals), was investigated by X-ray powder diffraction (pXRD), high-temperature pXRD, scanning electron microscopy (SEM) and electron microprobe analysis (EMPA). The average chemical composition obtained by EMPA is (wt. %): Nb2 O5 – 42.6; Ta2 O5 – 4.4; TiO2 – 9.2; UO3 – 4.4; ThO2 – 1.0; MnO – 1.3; FeO – 19.4; Y2 O3 – 16.6. The untreated (original) sample is X-ray amorphous. The sample remained amorphous after annealing at 400 ° C for 1 hour. The sample became almost fully crystalline after annealing at 700 ° C for 1 hour with an X-ray diffraction pattern similar to that of Fe-columbite (ICCD: 01-074-7356). Further annealing at 1000 ° C and higher temperatures caused changes in the phase composition of the sample. It was proposed that under self-irradiation a single-phase U-Th-bearing solid solution, based on monocrystalline Y-niobate, became metamict but remained homogeneous without evidence of solid solution destruction. However, this metamict solid solution is unstable under thermal treatment and recrystallization.